ANALYSIS OF FACTORS THAT AFFECT THE WAQF'S TRUST IN THE MAWARIDUSSALAM WAQF NAZHIR INSTITUTION - M. Guffar Harahap; Aswin Fahmi Darma; M. Radiansyah (CV. Barokah Publsiher, 2026)
This study aims to analyze the factors that affect the waqf's trust in the Mawaridussalam Waqf Nazhir Institution. Waqf trust is an important aspect in supporting the successful collection and management of waqf in a professional, transparent, and sustainable manner. This study uses a quantitative approach with the type of associative research. Data was obtained through the distribution of questionnaires to the selected waqif using the purposive sampling technique. Data analysis was carried out using the Structural Equation Modeling-Partial Least Squares (SEM-PLS) method with the help of SmartPLS 4.0 software. The results of the study show that transparency, accountability, professionalism of nazhir, and service quality are factors that play a role in building waqf trust in the Mawaridussalam Waqf Nazhir Institution. The implementation of good governance, information disclosure, and the ability of nazhir to manage waqf in a trustworthy manner are the basis for the formation of waqf confidence in the institution. The findings of this research are expected to be evaluation material for waqf managers in improving the quality of service, governance, and accountability so as to be able to strengthen public trust and optimize the collection and management of productive waqf to support the welfare of the people in a sustainable manner.